Model of Synergy Parents and Teachers in Character Education of High School Students - Darna, I Wayan; Suci, I Gede Sedana (research, training and philanthropy institution Natural Aceh, 2024)
The development of children's character is influenced by the synergy between the responsibilities of parents and teachers, as well as those of home, school, and community. This study aims to find a model of synergy or cooperation between parents and educators in helping adolescents develop character, kinship, discipline, and honesty. The subject of the study was SMA Negeri 3 Denpasar, using a descriptive qualitative research design. The informants were parents, vice principals, and teachers. The researcher is instrumental in this investigation. Techniques for collecting data include documentation, interviews, and observation. Data analysis methods include steps to reduce data, data visualization, and conclusions. The results of this investigation show that the synergy models or patterns applied in optimizing the roles of teachers and parents are 1) enforcing school regulations and 2) building communication and coordination between teachers and people. The implications of this pattern impact the success of character building in students to the maximum. Following up on the results of this study, regarding the program of activities implemented at home and school, parents and teachers must communicate effectively with each other.